Contributing Factors for Bone Metastasis in Uterine Cervical Cancer. Issue 7 (1st September 2013) - Yoon, Aera; Choi, Chel Hun; Kim, Ha-Jeong; Park, Jin-Young; Lee, Yoo-Young; Kim, Tae-Joong; Lee, Jeong-Won; Bae, Duk-Soo; Kim, Byoung-Gie
Abstract : Objective: The purpose of this study was to describe the clinical characteristics and to assess the contributing factors in patients developing bone metastasis in uterine cervical cancer. Methods: Two thousand thirteen patients had a diagnosis of uterine cervical cancer at Samsung Medical Center between June 1994 and December 2011. During the study period, 105 patients with bone metastasis were identified, and their clinicopathologic data were investigated retrospectively. Results: Among 105 patients with bone metastasis, 14 patients were excluded and 91 patients were evaluable. The median bone metastasis–free survival was 27 months (range, 0–279 months). The time to bone metastasis was significantly shorter in patients with adenocarcinoma than in patients with squamous cell carcinoma (median duration, 12 vs 29 months; P = 0.016). In addition, it was shorter in patients with stage IIB to stage IV disease than in those with stage I to stage IIA disease (15 vs 22 months; P = 0.02). The median survival after bone metastasis was 10 months, longer in the patients who received radiotherapy (± chemotherapy) than in the patients who received chemotherapy alone as a salvage therapy (12 vs 7 months; P = 0.01). Initial stage, number of bone metastases, location of involved bone, and coexisting metastatic lesion were not associated with the overall survival of the patients. Conclusions: Our study demonstrates that adenocarcinoma, advanced stage (IIB-IV) and initial multiple bone metastases contribute to earlier bone metastasis. Once bone metastasis was recognized, the survival of these patients was poor and no factors were identified to predict survival of those patients.